Role of Pap Smear in Screening of Infections and Malignancies: An Analytical Study in A Tertiary Care Centre - Mehak Reyaz; Nupur Nandi; Ritika Aggarwal (Medical Research and Its Applications Vol. 11, 2024)
Background: Cervical cancer is the fourth most common cancer in women. In India and other developing countries, cervical cancer is the leading cause of morbidity and mortality. Cancer cervix continues to be the most common genital carcinoma in India accounting for 80% of all female genital malignancies. In India, on an annual basis, about 1,32,000 cases are noted, with each year amounting to 74000 deaths in total, thus every 7th-minute cervical cancer claims the life of one woman. Pre-invasive lesions can spontaneously regress to normal or remain stable for a long period or progress to a higher degree of dysplasia. Cancer of the cervix is preventable if diagnosed at the pre-invasive stage with regular intervals of cytological screening by Papanicolaou (Pap) smears. The aim of the study is to analyse the pap reports in terms of normal findings, infections, premalignant lesions and invasive cancers. Methods: All women attending the outpatient department of gynaecology at TMMC and RC Moradabad, Uttar Pradesh over a period of 1 year from August 2017-18 presented with obstetrics and with white discharge per vagina were screened for cervical cancer using pap smear. All the smears were reported as per the 2014 Bethesda system. All the collected data were analyzed by using the SPSS tool and descriptive statistics were presented as frequencies and percentages. Results: Out of 1392, Pap smear reports ASCUS was reported in 27 cases (2%), LSIL in 27 cases (2%), HSIL in 15 cases (1%), malignant cells in 15 cases (1%) and normal including the infection is reported in 1308 cases (94%). Due to changes in lifestyle and changes in demographic profile in developing countries, non-communicable diseases are on the increase as an important health problem that requires effective control programs before, they become involved in their epidemic spread. The most common symptom in this study was white discharge per vagina accounting for 36%. Conclusions: Early cervical epithelial changes can be identified by a Pap smear test, which is the primary screening test for detection of precancerous cervical intraepithelial neoplasia and the early stage of invasive cervical cancer. The sensitivity of pap as a screening test can be increased with universal screening of all women attending gynecological OPD.